Radiative properties of argon–helium–nitrogen–carbon–cobalt–nickel plasmas used in CNT synthesis. (22nd January 2015) - Salem, D; Hannachi, R; Cressault, Y; Teulet, Ph; Béji, L
Abstract: This work presents the radiative properties of argon–helium–nitrogen–carbon–nickel–cobalt thermal plasmas by the computation of net emission coefficients (NECs) under the assumption of a local thermodynamic equilibrium and at temperature range 1000–20 000 K. These mixtures were often used in the study of carbon nanotubes (CNTs) synthesis with arc plasma which becomes one of the most useful techniques in terms of flexibility of carbon nanostructures produced with fewer defects. The values of NEC allow estimation of total radiation losses in plasmas, by taking into account the emission radiation resulting from the atomic continuum, the molecular continuum, the atomic lines and some molecular bands. Free–free transitions (Bremsstrahlung) and free–bound (electron–ion recombination), have been considered for the calculation of atomic continuum. For bound–bound transitions, natural, resonance, Van der Waals, Stark and Doppler effects have been taken into account in the calculation of the lines broadenings while the self-absorption of the resonance lines has been treated using their escape factors. Molecular continuum has been only considered for N2, C2 and CN molecules whereas we have only taken into account diatomic systems N2, , CN and C2 for the emission of the molecular bands. The results obtained show that even for low concentrations of Ni and Co in the plasma, the NECs are modified and considerably increase only at a low temperature ( T  < 8000 K) and the major contribution in the total radiation arises from the lines emission. However, the effect of the thickness of the plasma on plasma radiation has been analysed based on the self absorption phenomenon of resonance lines.